Peyorasi Kosa Kata Jawa Kuno dalam Bahasa Bali - Jayana, Ida Bagus Made Gesram Dwi (Javanese Language, Literature, and Culture Study Program, Universitas Gadjah Mada, 2024)
Balinese is one of the regional languages in the Indonesian archipelago. In its use, Balinese requires speakers to select words based on a complex system of linguistic levels. Over time, the Balinese language has inherited numerous words from other languages, primarily Old Javanese and Sanskrit. This study aims to examine linguistic phenomena, specifically pejoration or the process of semantic degradation, occurring in the vocabulary of Old Javanese that has been inherited into Balinese. Pejoration refers to the semantic shift of a term, wherein its meaning, initially refined or neutral, deteriorates into a coarser or less favorable connotation. The data for this research were derived from the Ādiparwa text. Primary data were obtained from the Ādiparwa Lontar manuscript in the collection of Griya Srama Tegallantang, Ubud, while secondary data consisted of research books, edited versions of the Ādiparwa text, as well as Balinese and Old Javanese dictionaries. The results reveal that at least five words from the Ādiparwa vocabulary have undergone pejoration. These words are /gawe/, /kurĕn, /mati/, /milu/, /mulih/. Analysis indicates that the causes of pejoration in the inheritance of Old Javanese into Balinese are attributed to two factors: changes in sociocultural contexts and differing interpretations among speakers of Old Javanese and Balinese regarding the usage of these words within the Balinese language. === Bahasa Bali merupakan salah satu bahasa daerah di Nusantara, dalam komunikasinya bahasa Bali menuntut pengunaan untuk mengunakan kata berdasarkan sistem tingkatan bahasa yang kompleks. Seiring perjalanan waktu bahasa Bali banyak mewarisi kata-kata dari bahasa lainya, utamanya bahasa Jawa Kuno dan Sanskerta. Penelitian ini bertujuan untuk meneliti terjadinya gejala linguistik berupa peyorasi atau pengasaran makna yang terjadi dalam kosa kata bahasa Jawa Kuno yang terwaris ke dalam bahasa Bali. Peyorasi merpakan proses perubahan makna sebuah ujaran, yang awalnya bersifat halus atau umum kemudian terjadi degradasi makna cenderung kasar. Sumber data yang digunakan dalam penelitian ini bersumber teks Ādiparwa. Data primer berupa Naskah Lontar Ādiparwa koleksi Griya Srama Tegallantang Ubud, dan data sekunder berupa buku-buku penelitian serta suntingan naskah Ādiparwa serta kamus bahasa Bali dan bahasa Jawa kuno. Hasil yang didapat yaitu, dari kosa kata Ādiparwa yang diambil, setidaknya telah terjadi proses peyorasi pada lima kata. Kelima kata tersebut yaitu /gawe/, /kurĕn, /mati/, /ilu/, /ulih/. Melalui pembahasan yang dilakukan, di dapat pula penyebab terjadinya peyorasi pada proses pewarisan bahasa Jawa Kuno ke dalam bahasa Bali disebabkan oleh dua faktor yaitu perubahan sosial budaya dan perbedaan tanggapan dalam masyarakat penutur bahasa Jawa Kuno dan Bali, terhadap pemakaian kata tersebut dalam bahasa Bali.